Impairment of resin cement application on the bond strength of indirect composite restorations - Jovito Adiel SKUPIEN; José Augusto Sedrez PORTO; Eliseu Aldrighi MÜNCHOW; Maximiliano Sérgio CENCI; Tatiana PEREIRA-CENCI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aims of this study were to evaluate the effect of immediate and delayed resin cement application on the microtensile bond strength of indirect composite resin restorations and, to evaluate adhesive strategies (for regular resin cement or humidity parameters for self-adhesive resin cement). Forty-five enamel/dentin discs (0.5 mm height and 10 mm of diameter) obtained from bovine teeth were divided into nine groups (n = 5). For regular cement, the variation factors were cementation technique at three levels (immediate cementation, 5 or 30 min after adhesive system application); and type of adhesive system at two levels (three- or two-step). For self-adhesive cement, the dentin moisture was the source of variation at three levels (normal, dry, or wet cementation). The specimens were submitted to microtensile bond strength (μTBS) testing using a universal testing machine. Data were analyzed by ANOVA, Tukey's test, and linear regression. Regular cement and three-step etch-and-rinse adhesive system showed the highest values of bond strength (25.21 MPa-30 min of delay). Only for this condition, three-step adhesive showed higher bond strength than the two-step adhesive. Nevertheless, the linear regression showed that irrespective of the strategy, the use of the two-step approach when compared with three-step adhesive system decreased μTBS (p < 0.001). The failure analysis showed predominant adhesive failures for all tested groups. All groups had comparable values of bond strength to bovine dentin when the same materials were used, even in suboptimal clinical conditions.